Policy Implementation Analysis of Mobile National Health Insurance for BPJS Health Participants in Sendangan Village, Sonder District - Margareth Rantung; Itje Pangkey; Fiona S. Tambuwun (Technium Social Sciences Journal, 2023)
This study aims to determine and describe how the Implementation of the National Health Insurance Mobile Policy for BPJS Health Participants in Sendangan Village, Sonder District. The approach used in this research is a qualitative approach with a descriptive type. The results of this study state that the Implementation of the National Health Insurance Mobile Policy for BPJS Health Participants in Sendangan Village, Sonder District has not been implemented properly and effectively, where: 1) Many people do not know and do not understand about this policy, because there has been no socialization from the government and related agencies, which is also due to the lack of relations between the government and related agencies in this case BPJS Health. Coordination in this policy has not been effective, 2) the ability of the community is felt to be lacking to understand how to use the Mobile National Health Insurance because there is no information obtained by the community, the community also does not know the purpose of this policy and the benefits that the community can get from this policy 3) many people do not have facilities in the form of supporting devices and internet data needs that are not sufficient for the National Health Insurance Mobile Application, and there are also frequent system errors in the application due to frequent updates of the latest version, which results in many devices that cannot easily access the application.